The analysis of cable and catenary structures - Broughton, Peter (Thomas Telford, 1994)
This work provides sound practical guidance on cable and catenary structural systems. In a clear and concise manner it deals with the complicated subject of exact formulation in the theoretical treatment of these systems when subjected to large charges in geometry.